Zippy the ant ... loses her way - Lambert, Jonathan ([New York] : Reader's Digest Association, 1994)
The reader lifts flaps to help Zippy find her way.
"Lift-the-flap-book"
Keywords: Children's stories; Toy and movable books -- Specimens